When the law is unclear: challenges and opportunities for data and information exchange in the Tigris-Euphrates and Indus river basins - Qaraman M. Hasan; Sarkawt Ghazi Salar; Durgeshree Raman; Sam Campbell; Ibrahim Qasim Palani (Water Policy, 2023)
Data and information exchange are vital for long-term transboundary water cooperation. However, many transboundary river basins lack regular data exchange between riparian States. In many cases, this is simply a feature of the generally fragmented nature of transboundary water cooperation; in others, transboundary river basin data sharing may be withheld for geopolitical reasons. The Tigris-Euphrates and Indus river basins are among the most highly politicized river basins globally. Cooperation between riparians is complicated by a lack of certainty regarding data, information exchange and legal obligations, as upper riparians in both basins have persistently objected to the customary law of international watercourses. With reference to international water law, this article ascertains the level of data and information exchange in these two basins, both through formal and informal structures, as well as prevalent obstacles and the institutional and technological responses to them. Despite significant challenges, the authors argue that technological advances can stimulate enhanced riparian cooperation. HIGHLIGHTS The existing legal frameworks in these basins provide a platform for data and information exchange to take place.; The greater cooperation and participation through quality data and information exchange between and within riparian states would mean that IWRM could be meaningfully implemented.; Implementing international law principles depend on the level of cooperation among watercourse states.; Sharing data with local people in the basins contributes to better regional and international cooperation.;